A New Series of Antibacterial Nitrosopyrimidines: Synthesis and Structure–Activity Relationship. Issue 1 (21st November 2014) - Olivella, Monica; Marchal, Antonio; Nogueras, Manuel; Melguizo, Manuel; Lima, Beatriz; Tapia, Alejandro; Feresin, Gabriela E.; Parravicini, Oscar; Giannini, Fernando; Andujar, Sebastián A.; Cobo, Justo; Enriz, Ricardo D.
<x xml:space="preserve">Abstract</x> New nitrosopyrimidines were synthesized and evaluated as potential antibacterial agents. Different compounds structurally related with 4, 6‐bis(alkyl or arylamino)‐5‐nitrosopyrimidines were evaluated. Some of these nitrosopyrimidines displayed significant antibacterial activity against human pathogenic bacteria. Among them compounds 1c, 2a–c, and 9a–c exhibited remarkable activity against methicillin‐sensitive and ‐resistant Staphylococcus aureus, Escherichia coli, Yersinia enterocolitica, and Salmonella enteritidis. A detailed structure–activity relationship study, supported by theoretical calculations, aided us to identify and understand the minimal structural requirements for the antibacterial action of the nitrosopyrimidines reported here. Thus, our results have led us to identify a topographical template that provides a guide for the design of new nitrosopyrimidines with antibacterial effects.